Determining Essential Fitness and Motor Skill Parameters for Talent Identification in 12-Year-Old Girls: A Comparison of Machine Learning-Based Feature Extraction Techniques - Muazu Musa, Rabiu; Mat-Rasid, Siti Musliha; Lee Low, Jeffrey Fook; Elumalai, Gunathevan; Shahril, Mohd. Izwan; Ismail Ahmad, Mohamad Azri; Kosni, Norlaila Azura (International Journal of Intelligent Systems and Applications in Engineering, 2024)
A successful talent identification program relies on the assessment and mapping of relevant parameters for the evaluation of an athlete’s ability. Physical fitness and motor-skill parameters are performance variables that contribute to success in a variety of sports. Although these parameters are prerequisites for any sporting event, their requirements may differ depending on the athletes’ level and age. The present investigation endeavors to identify essential physical fitness and motor skill-related parameters for talent identification in 12-year-old girls. A total of 236 girls were recruited from different schools in Malaysia and completed a standard test for physical fitness and motor skills that constituted of 30-meter run, step test, 1-minute curl up, hand grip, agility T-test, stork balance stand test, and standing broad jump test. Two different feature extraction techniques viz. Symmetrical Uncert Attribute Evaluation (SymmU) and Recursive Feature Elimination (RFE) were employed to determine the important parameters that could be considered for talent identification in 12-year-old girls. Both the SymmU and RFE demonstrated four sets of parameters worthy of consideration. There was agreement in the selection of three parameters across the two techniques (sit and reach, agility, and stork balance stance test). However, SymmU revealed the standing broad jump as the fourth essential parameter, while RFE indicated a 1-minute curl up. Overall, these tests are shown to be essential for consideration during talent identification programs for 12-year-old girls. The identified parameters provide actionable knowledge for coaches and sports organizations, fostering the development of the next generation of elite female athletes.